Public Health Care Management: A Critical Study Over the Level of Satisfaction of Select Users - Ahmed, Marjina; Sikidar, Sujit (Journal of Coastal Life Medicine, 2023)
The level of a patient's happiness using the medical the assistance they got from healthcare supplier is measured by service user's satisfaction index. Among the key elements affecting how well a healthcare institution performs is the pleasure of its service users. The goal of this study was to assess how satisfied health care consumers were with their experiences, taking into account how the doctor's actions affected that relationship. The study's objective is to evaluate how successfully the private health sectors of Guwahati City provide services including preventive care, diagnostic testing, and 24-hour access to medicine. Present study employed a study design for a descriptive survey. Service customers who used the outpatient departments of five private medical centers in Guwahati City were the intended audience. The selected population's 290 sample respondents were selected by a straightforward random sampling procedure. The dependability scales were calculated utilizing Cronbach's Alpha. The results of the study were investigated using regression analysis, which looked at service user satisfaction with healthcare services. For the study, the SPSS Hayes procedure was employed. The main conclusions of the regression study support the notion that medical services, such as laboratory and diagnostic care, preventative health care, and 24-hour access to drugs, have an important and beneficial effect on service satisfaction among users. The study specifically contends that the actions of doctors considerably modify the impact of health care services on the degree to which service consumers are satisfied with the accessibility of health services in hospitals. Regarding laboratory and diagnostic treatment, preventative healthcare, and a 24-hour medical facility, the level of satisfaction was satisfactory. The results of the investigation support the statistical significance of the suggested research questions.